Oral microbial dysbiosis and its performance in predicting oral cancer. (4th July 2020) - Su, Shih-Chi; Chang, Lun-Ching; Huang, Hsien-Da; Peng, Chih-Yu; Chuang, Chun-Yi; Chen, Yi-Tzu; Lu, Ming-Yi; Chiu, Yu-Wei; Chen, Pei-Yin; Yang, Shun-Fa
Abstract: Dysbiosis of oral microbiome may dictate the progression of oral squamous cell carcinoma (OSCC). Yet, the composition of oral microbiome fluctuates by saliva and distinct sites of oral cavity and is affected by risky behaviors (smoking, drinking and betel quid chewing) and individuals' oral health condition. To characterize the disturbances in the oral microbial population mainly due to oral tumorigenicity, we profiled the bacteria within the surface of OSCC lesion and its contralateral normal tissue from discovery ( n = 74) and validation ( n = 42) cohorts of male patients with cancers of the buccal mucosa. Significant alterations in the bacterial diversity and relative abundance of specific oral microbiota (most profoundly, an enrichment for genus Fusobacterium and the loss of genus Streptococcus in the tumor sites) were identified. Functional prediction of oral microbiome shown that microbial genes related to the metabolism of terpenoids and polyketides were differentially enriched between the control and tumor groups, indicating a functional role of oral microbiome in formulating a tumor microenvironment via attenuated biosynthesis of secondary metabolites with anti-cancer effects. Furthermore, the vast majority of microbial signatures detected in the discovery cohort was generalized well to the independent validation cohort, and the clinical validity of these OSCC-associated microbes was observed and successfully replicated. Overall, our analyses reveal signatures (a profusion of Fusobacterium nucleatum CTI-2 and a decrease in Streptococcus pneumoniae ) and functions (decreased production of tumor-suppressive metabolites) of oral microbiota related to oral cancer. Abstract : We demonstrated that oral microbiota is compositionally and functionally associated with the development of oral cancer. Our study implicates specific oral microbes as a potential biomarker for early diagnosis and prognosis monitoring of this deadly malignancy.